Racial Discrimination and Adverse Birth Outcomes: An Integrative Review. (13th October 2016) - Alhusen, Jeanne L.; Bower, Kelly M.; Epstein, Elizabeth; Sharps, Phyllis
Abstract : Introduction: This article presents an integrative review of the literature examining the relationship between racial discrimination and adverse birth outcomes. Methods: Searches for research studies published from 2009 to 2015 were conducted using PubMed, CINAHL, Scopus, PsycINFO, Web of Science, and Embase. Articles were assessed for potential inclusion using the Preferred Reporting Items for Systematic Review and Meta‐Analyses (PRISMA) 2009 framework. Results: Fifteen studies met criteria for review. The majority of the studies found a significant relationship between racial discrimination and low birth weight, preterm birth, and small for gestational age. Each of the studies that examined more proximal variables related to birth outcomes such as entry into prenatal care, employment opportunities, neighborhood characteristics, or inflammatory markers found significant associations between the specific variables examined and racial discrimination. Participants in qualitative studies discussed experiences of institutional racism with regard to several components of prenatal care including access and quality of care. Discussion: Racial discrimination is a significant risk factor for adverse birth outcomes. To best understand the mechanisms by which racial discrimination impacts birth outcomes, and to inform the development of effective interventions that eliminate its harmful effects on health, longitudinal research that incorporates comprehensive measures of racial discrimination is needed. Health care providers must fully acknowledge and address the psychosocial factors that impact health outcomes in minority racial/ethnic women.